(untitled) (The Review of Diabetic Studies, 2025)
Background: Infectious diseases remain a significant public health challenge globally. Family physicians, as frontline primary care providers, play a critical role in preventing disease contraction and limiting community transmission through prevention, early detection, patient education, and community collaboration. This study aimed to assess the strategies implemented by family physicians to reduce the spread of infectious diseases. Methods: A descriptive analytical cross-sectional study was conducted among 240 practicing family physicians. Data were collected using a validated, self-administered questionnaire covering demographic characteristics, infection prevention and control measures, vaccination activities, patient education strategies, antimicrobial stewardship, and surveillance practices. Descriptive statistics were used to summarize the data, and inferential analyses were performed to examine associations. Results: The majority of participants reported high adherence to fundamental infection control measures: routine hand hygiene (89.2%), regular clinic surface disinfection (85.8%), and use of personal protective equipment (82.5%). Most physicians actively recommended vaccinations (85.0%) and routinely reviewed immunization status (80.0%). Patient education was widely practiced, particularly on hand hygiene (90.8%) and antibiotic misuse prevention (84.2%). While antimicrobial stewardship was strong, with 87.5% prescribing antibiotics only when indicated, engagement in surveillance activities—such as reporting notifiable diseases (68.3%) and monitoring local infection trends (61.7%)—was comparatively lower. Conclusion: Family physicians are actively engaged in key strategies to prevent and control infectious diseases, especially in infection prevention, vaccination promotion, and patient education. However, gaps remain in systematic surveillance and broader community-level campaign participation. Enhancing training, strengthening systemic support, and improving integration with public health systems are recommended to optimize the role of family physicians in infectious disease prevention and preparedness.